2019
DOI: 10.31219/osf.io/vp2f6
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Triarchic or Septarchic? - Uncovering the Triarchic Psychopathy Measure’s (TriPM) Structure

Abstract: Tested factor structure of Triarchic Psychopathy Measure using EFA and CFA across multiple samples.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…So far, reports shedding light on the measurement model of the TriPM, such as using factor analysis, are sparse. The studies that are available do not provide clear evidence for the three dimensions in the original measurement model, based on standard criteria of good model fit (8,(49)(50)(51). Furthermore, the items of the TriPM display varying associations to the hypothesized factors, with several items loading weakly to the intended factor, as well as cross-loading to the other factors (8,50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, reports shedding light on the measurement model of the TriPM, such as using factor analysis, are sparse. The studies that are available do not provide clear evidence for the three dimensions in the original measurement model, based on standard criteria of good model fit (8,(49)(50)(51). Furthermore, the items of the TriPM display varying associations to the hypothesized factors, with several items loading weakly to the intended factor, as well as cross-loading to the other factors (8,50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of association between the TriPM Disinhibition and Boldness may put to question if all domains are meaningfully related within the same construct. Roy et al (51,53), by performing an item-level factor structure analysis of the TriPM, found the current three domains to be inherently multidimensional and instead proposed a 7-factor structure based of the psychometric instrument. They suggest that the psychometric weaknesses of the instrument, such as lack of internal construct validity, risk leading to statistical washout effects and a theoretical over-simplification of the psychopathic personality.…”
Section: Discussionmentioning
confidence: 99%
“…So far, reports shedding light on the measurement model of the TriPM, such as using factor analysis, are sparse. The studies that are available do not provide clear evidence for the three dimensions in the original measurement model, based on standard criteria of good model fit (8,(49)(50)(51). Furthermore, the items of the TriPM display varying associations to the hypothesized factors, with several items loading weakly to the intended factor, as well as cross-loading to the other factors (8,50).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the lack of association between the TriPM Disinhibition and Boldness may put to question if all domains are meaningfully related within the same construct. Roy et al (51,53), by performing an item-level factor structure analysis of the TriPM, found the current three domains to be inherently multidimensional and instead proposed a 7-factor structure based of the psychometric instrument. They suggest that the psychometric weaknesses of the instrument, such as lack of internal construct validity, risk leading to statistical washout effects and a theoretical over-simplification of the psychopathic personality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation